Stem cell-like T cell depletion in the recurrent head and neck cancer immune microenvironment - Linda Chen; Nancy Lee; Reith Sarkar; Nora Katabi; Yanyun Li; Luc Morris; Richard Wong; Eric Sherman; Jorge S. Reis-Filho; Travis Hollmann; Nadeem Riaz (OncoImmunology)
Human papilloma virus (HPV)-related oncogenesis in head and neck cancer establishes a local microenvironment rich with immune cells, however the composition of the microenvironment in recurrent disease following definitive treatment is poorly understood. Here, we investigate the composition and spatial relationships between tumor and immune cells in recurrent head and neck cancer following curative intent chemoradiotherapy. Multiplexed immunofluorescence with 12 unique markers, through two multiplex immunofluorescent panels, was performed to evaluate 27 tumor samples including 18 pre-treatment primary and 9 paired recurrent tumors. Tumor and immune cell populations were phenotyped and quantified using a previously validated semi-automated digital pathology platform for cell segmentation. Spatial analysis was conducted by evaluating immune cells within the tumor, peri-tumoral stroma, and distant stroma. Initial tumors in patients with subsequent recurrence were found to be enriched in tumor associated macrophages and displayed an immune excluded spatial distribution. Recurrent tumors after chemoradiation were hypo-inflamed, with a statistically significant reduction in the recently identified stem-like TCF1+ CD8 T-cells, which normally function to maintain HPV-specific immune responses in the setting of chronic antigen exposure. Our findings indicate that the tumor microenvironment of recurrent HPV-related head and neck cancers displays a reduction in stem-like T cells, consistent with an immune microenvironment with a reduced ability to mount T-cell-driven anti-tumor immune responses.